2022
DOI: 10.1007/978-3-031-17899-3_7
|View full text |Cite
|
Sign up to set email alerts
|

Weakly Supervised Intracranial Hemorrhage Segmentation Using Hierarchical Combination of Attention Maps from a Swin Transformer

Abstract: Intracranial hemorrhage (ICH) is a life-threatening medical emergency caused by various factors. Timely and precise diagnosis of ICH is crucial for administering effective treatment and improving patient survival rates. While deep learning techniques have emerged as the leading approach for medical image analysis and processing, the most commonly employed supervised learning often requires large, high-quality annotated datasets that can be costly to obtain, particularly for pixel/voxel-wise image segmentation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Furthermore, comparing the proposed weakly supervised ICH segmentation framework for two Swin transformers based on (1) binary classification (presence of hemorrhage or not) and (2) multi-label classification (detailed ICH subtypes and with/without ICH), we found that binary classification helped better focus the network attention on the ICH regions. In this paper, we further extended our previous study (Rasoulian et al, 2022) with three main contributions. First, inspired by the gradient-weighted class activation mapping (Grad-CAM) (Selvaraju et al, 2017), we proposed a novel attention visualization technique, called HGI-SAM (Head-wise Gradient-infused Self-Attention Mapping), by performing head-wise weighing of self-attention obtained from the Swin transformer using the gradient of the target class.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Furthermore, comparing the proposed weakly supervised ICH segmentation framework for two Swin transformers based on (1) binary classification (presence of hemorrhage or not) and (2) multi-label classification (detailed ICH subtypes and with/without ICH), we found that binary classification helped better focus the network attention on the ICH regions. In this paper, we further extended our previous study (Rasoulian et al, 2022) with three main contributions. First, inspired by the gradient-weighted class activation mapping (Grad-CAM) (Selvaraju et al, 2017), we proposed a novel attention visualization technique, called HGI-SAM (Head-wise Gradient-infused Self-Attention Mapping), by performing head-wise weighing of self-attention obtained from the Swin transformer using the gradient of the target class.…”
Section: Introductionmentioning
confidence: 75%
“…In their approach, a mean Dice of 0.58 was reached for the lesion bounding boxes. Unfortunately, to the best of our knowledge, aside from our earlier work (Rasoulian et al, 2022), self-attention, especially with a Swin transformer, has not yet been explored for weakly supervised ICH segmentation, and we intend to further improve our proposed framework to boost the performance.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The regression head reduces the dimensionality from C (de,3) = 288 to 128, and then 1. Based on this recently introduced mechanism, DL models were developed for medical image segmentation (Naderi et al, 2022;Rasoulian et al, 2023), change detection for remote sensing data (Fazry et al, 2023), and video action recognition (Wasim et al, 2023). We build our model on focal modulation networks and extend their applications in Geoscience.…”
Section: Model Architecturesmentioning
confidence: 99%
“…In our previous work (Rasoulian et al, 2022), we employed a Swin transformer to perform CT-based detection and weakly supervised segmentation of ICH for the first time. More specifically, we obtained ICH segmentation by fusing hierarchical self-attention maps generated from a Swin transformer that was trained using categorical labels for ICH detection.…”
Section: Introductionmentioning
confidence: 99%